Maxillary Antrostomy Patency Following Intraoperative Use of Spray Cryotherapy - Trombitaș, Veronica (J Clin Med, 2019)
Objectives/Hypothesis: Stenosis of the middle meatus antrostomy (MMA) represents a major cause of recurrent disease following endoscopic sinus surgery (ESS). Various strategies have been developed to prevent the occurrence of MMA stenosis. The aim of the present study was to evaluate the effects of spray cryotherapy (SC) on nasal wound healing following ESS. Methods: This is a prospective within-subject, randomized, and controlled trial. Twenty-six patients submitted to bilateral ESS with chronic rhinosinusitis without polyps were included. Following surgery, patients were randomized to receive SC on one side and saline contralaterally. Outcomes were represented by MMA diameter and area, histology of nasal mucosa, and nasal symptoms. Variables were assessed at 3 and 12 months postoperatively. Results: The MMA size in the SC group at 3 and 12 months (area—0.578 ± 0.1025 cm(2), diameter—0.645 ± 0.1024 cm; 0.605 ± 0.1891 cm(2), 0.624 ± 0.0961 cm, respectively) was significantly larger (p = 0.000) than in the control group. Histology established that cell infiltration, goblet cells, edema, and epithelial hyperplasia were prominent and persistent in the control side compared to the SC side. Nasal obstruction and discharge were significantly improved in the SC group compared to the control group. Conclusion: SC is a promising therapy following ESS, since it precludes MMA stenosis and decreases inflammation, edema, and goblet cell hyperplasia.